PEMBINAAN PADUAN SUARA SEBAGAI MEDIA PENGEMBANGAN KETERAMPILAN DAN KARAKTER WARGA BINAAN DI LAPAS KELAS III RANGKASBITUNG - Ernanda Pratama, Irham; Rizal, Syamsul; Hadiyatno; Maulana, Adi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Guidance activities in correctional instututions are one of the efforts to help inmates develop skills and improve their behavior during their rehabilitation period. One form of guidance activity that can be implemented is music arts, especially choir activities. This study aims to determine the implementation of choir guidance activities and their impact on the vocal abilities and attitudes of inmates at Class III Rangkasbitung Correctional Institution. This study used a descriptive qualitative approach with data collection techniques in the form of observation, documentation, and direct involvement during the activity process. The activities were carried out from March to May, 2025 with training sessions held twice a week, every Wednesday and Friday. The materials provided included basic vocal techniques such as breathing, articulation, and intonation, which were then applied to the songs “Indonesia Raya,” “Tanah Airku”, and “Manuk Dadali”. The results showed that choir guidance activities had a positive impact in inmates. Participants showed improvement in singing abilities, especially in articulation, intonation, and vocal harmony. In addition, this activity also increased inmates’ self-confidence, participation, and enthusiasm during the training sessions. Some participants who were initially passive became more confident to perform and actively participate in group activities. Although there were obstacles, such as difficulties in memorizing song lyrics, these challenges could be overcome through repeated practice and facilitator assistance. Therefore, choir guidance activities can be considered an effective arts-based rehabilitation program to support the inmate development process in correctional institutions.